Molecular Anchoring with 4-Mercaptobenzoic Acid and 4-Aminothiophenol for Using Active Nanorods in the Detection of Dopamine. (1st December 2022) - Ramírez, Sara; Díaz, Fernando; Silva, Carlos P.; Pavez, Jorge; Silva, J. Francisco
Abstract : The incorporation and effective anchorage of gold nanorods in a gold (111) substrate is applied to electrochemical systems to detect dopamine. Gold nanorods (AuNRs) were synthesized in dispersion. They were then incorporated in a metal substrate mediated by self-assembled monolayers (SAMs) which act as structural anchors. Two molecular anchors, 4-mercaptobenzoic acid (4-MBA) and 4 aminothiophenol (4-ATP) are compared by means of the charge density (Q) in desorption of the SAMs, where 4-MBA presented a greater coverage on the metal surface. Both SAMs allowed the effective confinement and communication of the nanostructure to a greater or lesser extent. Characterizations were made to confirm the constructed system. First, the nanostructures synthesized in dispersion were characterized by UV-visible spectroscopy, Transmission electron microscopy and atomic force microscopy. Second, an electrochemical characterization of the working electrodes include impedance was made. The results focus on the impact of the molecular anchor on the activity of the electrochemical sensor, it was determined. Reducing the charge transfer resistance (by at least 90% with appropriate SAMs) of molecularly anchored gold nanorods increases the sensitivity of the electrochemical sensor (at least 20%), the detection of dopamine was studied by square wave voltammetry through a calibration curve, where better sensitivity and detection limit was obtained with the Au/4-MBA/AuNRs system compared to Au/4-ATP/AuNRs.